MDDT model driven development tool as aid for Learning Programming Fundamentals - Dy, Bryle; Laureano, Philip; Liu, Michael David; Syliongka, Leif Romeritch; Roxas, Rachel Edita (Philippine computing journal)
In conventional ways, students, who are learning how to program, struggle with learning the syntax conventions of a particular programming language more rather than learning how to program logically...